13.8k views
11 votes
Find h(-2) for h(r)= r^2 - 7r + 2

Find h(-2) for h(r)= r^2 - 7r + 2-example-1
User Loveen
by
5.8k points

2 Answers

8 votes

Answer:

34

Explanation:

Find h(-2) for h(r)= r^2 - 7r + 2

Simply put in -2 for 'r'

(-2)^2 - 7(-2) + 2 =

4 - - 28 + 2 =

4+ 28 + 2 = 34

User Santosh Kumar
by
4.9k points
9 votes

The value of h(-2) = 20.

To find h(-2) for h(r) = r^2 - 7r + 2, we need to substitute -2 for r in the given equation and solve for h(-2).

h(-2) = (-2)^2 - 7(-2) + 2

h(-2) = 4 + 14 + 2

h(-2) = 20

Therefore, h(-2) = 20.

User Joe Pitz
by
6.4k points